Examining the effect of KM strategy on knowledge performance: the mediating role of sharing behaviour and enablers. (2018) - Singh, Pooja K.; Rao, M.K.
In present knowledge era, sustaining competitive edge and managing excellence requires organisations to develop their strategic orientation towards efficiency, effectiveness and performance. The present study sought to examine the effect of KM strategy (balanced view) on behavioural intention toward knowledge sharing and its subsequent impact on knowledge performance. Several research hypotheses have been formulated and tested empirically to justify proposed framework based on profound theoretical annotations. Structural equation modelling (SEM) using SPSS 22, PROCESS macro and AMOS 20 were applied to test the prepositions after collecting data from knowledge-intensive business firms. The study provides empirical evidences for the relationship among KM strategy (tacit, explicit), behavioural intent to share knowledge and performance. A later section of the study offers theoretical and managerial implications followed by limitations, suggestions and concluding remark.